Legal Status of Recruited Children in Armed Conflict - Emiteg, Naser Ben aros; Haj Ibrahim, Badruddin (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at sheds light on the legal status of child soldiers involved in armed conflicts before they reach the age of conscription. Actually, there is no armed conflict passing without the participation of underage children in it. Moreover, there is a problem represented in the lack of clarity of the legal status of child soldiers participating in armed conflicts, upon capturing them or arresting them. Therefore, the question is ’What is the protection granted to them according to this legal status?’. This study tries to know and determine the identity of children with their legal status in the event of their conscription. If this happens, it regards a violation of international law. Furthermore, the study endeavored to clarify the protection granted to children in case of their captivity, because their humanitarian status differs from adult fighters. In addition, this study discussed how they are treated, as well as to clarify their criminal responsibility for the crimes they committed during the period of their recruitment. Accordingly, the researcher relied on the descriptive analytical approach to study the rules of international law and the texts of international charters and treaties that prohibit the recruitment and analysis of children in armed conflicts. In addition to the inductive approach was used to highlight the rules of link between the legal status of a child soldier and his criminal responsibility for his actions during the period of his recruitment. The study concluded with a set of findings, the most important of which are: the legal status of child soldiers is based on the availability of two basic conditions. Therefore, they enjoy of legal protection, whether the protection is general for prisoners of war, or special protection for civilian children. In addition, the legal status of child soldiers who have not reached the age of recruitment do not take in account for their criminal responsibility for their acts committed during the period of their conscription. Nevertheless, from other hand, there is no way to punish them, given their dual status as victims and perpetrators of a crime alike, according to the rules of international humanitarian law. However, the matter is different with regard to the internal judiciary of states.